Comparative Analysis of Vertebroplasty and Kyphoplasty for Osteoporotic Vertebral Compression Fractures - Bozkurt, Melih (Korean Society of Spine Surgery, 2014)
STUDY DESIGN: A retrospective study. PURPOSE: The aim of this study is to compare the efficacy and outcome of vertebroplasty compared with unipedicular and bipedicular kyphoplasty for the treatment of osteoporotic vertebral compression fractures in terms of pain, functional capacity and height restoration rates. OVERVIEW OF LITERATURE: The vertebroplasty procedure was first performed in 1984 for the treatment of a hemangioma at the C2 vertebra. Kyphoplasty was first performed in 1998 and includes vertebral height restoration in addition to using inflation balloons and high-viscosity cement. Both are efficacious, safe and long-lasting procedures. However, controversy still exists about pain relief, improvement in functional capacity, quality of life and height restoration the superiority of these procedures and assessment of appropriate and specific indications of one over the other remains undefined. METHODS: Between 2004 and 2011, 296 patients suffering from osteoporotic vertebral compression fracture underwent 433 vertebroplasty and kyphoplasty procedures. Visual analogue scale (VAS), the Oswestry Disability Index (ODI) and height restoration rates were used to evaluate the results. RESULTS: Mean height restoration rate was 24.16%±1.27% in the vertebroplasty group, 24.25%±1.28% in the unipedicular kyphoplasty group and 37.05%±1.21% in the bipedicular kyphoplasty group. VAS and ODI scores improved all of the groups. CONCLUSIONS: Vertebroplasty and kyphoplasty are both effective in providing pain relief and improvement in functional capacity and quality of life after the procedure, but the bipedicular kyphoplasty procedure has a further advantage in terms of height restoration when compared to unipedicular kyphoplasty and vertebroplasty procedures.